2007
DOI: 10.1007/s10336-007-0132-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of white stork (Ciconia ciconia) migratory phenology in the Iberian Peninsula

Abstract: In contrast to the attention attracted by temporal trends of phenology, the spatial patterns of arrivals, departures or stays of trans-Saharan birds are still nowadays largely unknown in most of their European breeding areas. In the case of the white stork (Ciconia ciconia), some studies have attempted to describe its migratory patterns throughout some European countries but, to our knowledge, no one has related these patterns to some kind of explanatory variable which offers an ecologically-based explanation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 46 publications
1
31
0
1
Order By: Relevance
“…In fact, breeders are not totally attached to their nest until egg laying. In addition, some pairs have not yet arrived in the breeding zone in February, March, and even April (Prieto 2002;Gordo et al 2007;Vergara et al 2007a). However, later in the breeding season, when chicks are 23 days old, they are able to thermoregulate (Tortosa and Castro 2003), and consequently parents may leave them alone in the nest while they are foraging (Tortosa and Villafuerte 1999).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, breeders are not totally attached to their nest until egg laying. In addition, some pairs have not yet arrived in the breeding zone in February, March, and even April (Prieto 2002;Gordo et al 2007;Vergara et al 2007a). However, later in the breeding season, when chicks are 23 days old, they are able to thermoregulate (Tortosa and Castro 2003), and consequently parents may leave them alone in the nest while they are foraging (Tortosa and Villafuerte 1999).…”
Section: Discussionmentioning
confidence: 96%
“…We selected these six colonies to obtain a representative range of breeding dates in Spain because this species shows a great variation in the arrival dates among zones (Gordo et al 2007). In order to avoid disturbance of breeding birds and bias on data, a few nests randomly selected within each colony were controlled from the same point away from the colony during a fixed time (2 h) in each survey.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, populations from SW Spain are notably earlier than those from the rest of the country (see mean arrivals in Table 1). The geographical patterns of the arrival dates of the White Stork were not clear (Gordo et al 2007b) and did not allow an easy and objective division of Spain into an early and late region, respectively. For the Nightingale, the distribution of arrival dates was narrow (see low standard deviation in Table 1), i.e.…”
Section: Bird Phenological Datamentioning
confidence: 97%
“…Under such conditions, a density dependence in reproductive success is likely to occur, which has already been reported for different European populations of white stork (Barbraud et al 1999;Sasvári et al 1999). It has also been demonstrated that storks from areas of high breeding densities arrive earlier in spring, indicating that intense competition takes place for attractive nesting territories (Gordo et al 2007). Finally, there is strong empirical evidence for the fitness benefits associated with early arrival of storks (Tryjanowski et al 2004; but see Janiszewski et al 2013), which suggests that delayed arrival may coincide with less favourable environmental conditions and, possibly, with lower food availability.…”
Section: Introductionmentioning
confidence: 99%